Synthesis of novel phenoxyacetohydrazide compounds and evaluation therapeutic potential exhibit as anti-inflammatory and anti-angiogenic - Mohammed, Yasser Hussein Issa; Shntaif, Ahmed Hassen; Alghamdi, Saad; Mansour, Ahd A.; Qusty, Naeem F.; Sindi, Azhar S.; Babalghith, Ahmad O.; Bamagous, Ghazi A.; Abu-Seer, Eman Adnan (PLOS ONE, 2025)
This study aimed to design, synthesize, and evaluate novel morpholine-substituted phenoxyacetohydrazide derivatives as potential anti-inflammatory and anti-angiogenic agents. The compounds were synthesized and characterized by FTIR, NMR, mass spectrometry, and elemental analysis. In silico molecular docking revealed that compound 6e exhibited strong binding affinities toward vascular endothelial growth factor (VEGF), cyclooxygenase-1 (COX-1), and cyclooxygenase-2 (COX-2), with docking scores of –13.1622, –12.5301, and –12.6705 (kcal/mol) respectively. The in vitro anti-inflammatory activity, assessed via the human red blood cell (HRBC) membrane stabilization assay, showed that compound 6e achieved an IC₅₀ value of 155 μg/mL, indicating potent efficacy. Additionally, 6e demonstrated significant anti-angiogenic activity in both in vivo and ex vivo chick chorioallantoic membrane (CAM) models, inhibiting VEGF-induced angiogenesis in a dose-dependent manner and markedly reducing microvessel density and vessel length. In a rat model of alkali-induced corneal neovascularization, compound 6e substantially suppressed neovascular growth. Moreover, in the carrageenan-induced paw edema model, it effectively reduced edema, neutrophil infiltration, and myeloperoxidase activity. Collectively, these findings position compound 6e as a promising dual-action therapeutic candidate for treating chronic inflammation and pathological angiogenesis. This study underscores the potential of systematically designed phenoxyacetohydrazide scaffolds as multi-targeted therapeutic agents.